2022
DOI: 10.3390/nu15010201
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Theaflavins on the Kidney of Mice with Type II Diabetes Mellitus

Abstract: Diabetic nephropathy, primarily caused by advanced glycation end products (AGEs), is a serious complication resulting from type 2 diabetes mellitus (T2DM). Reportedly, theaflavins (TFs) can improve diabetic nephropathy; however, the underlying molecular mechanism is not fully clear. In this study, T2DM mice were treated with different concentrations of TFs by gavage for 10 weeks to investigate the effect of TFs on diabetic nephropathy and their potential molecular mechanism of action. Biochemical and pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Comparable to metformin, TFs decrease casual blood glucose, fasting blood glucose, and serum HbA1c levels, and ameliorate IGT in diabetic mice. Among TFs, TF3 exhibits the most potent hypoglycemic effect [ 53 , 54 , 55 , 56 ]. Clinical studies have reported that TFs significantly reduce the fasting and postprandial blood glucose level in prediabetics [ 54 , 57 , 58 ].…”
Section: Effects Of Tfs On Glucose Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparable to metformin, TFs decrease casual blood glucose, fasting blood glucose, and serum HbA1c levels, and ameliorate IGT in diabetic mice. Among TFs, TF3 exhibits the most potent hypoglycemic effect [ 53 , 54 , 55 , 56 ]. Clinical studies have reported that TFs significantly reduce the fasting and postprandial blood glucose level in prediabetics [ 54 , 57 , 58 ].…”
Section: Effects Of Tfs On Glucose Metabolismmentioning
confidence: 99%
“…Further, they inhibit the accumulation of AGEs, ROS, and inflammatory factors, thereby ameliorating diabetes mellitus and its complications, such as diabetic nephropathy. Moreover, TFs have been shown to be more effective than metformin at the same oral dose (150 mg/kg) [ 55 , 82 , 83 ]. In T2DM patients, TFs were found to upregulate the mRNA and protein expression of sirtuin1 (SIRT1), thereby enhancing insulin sensitivity, inhibiting hyperglycemia, and reducing oxidative stress [ 84 ].…”
Section: Effects Of Tfs On Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Gothandam et al reported that theaflavins have antidiabetic potential by improving the activity of enzymes related to glucose metabolism in diabetic rats due to their antioxidant properties. Wang et al found that theaflavins may improve kidney damage in diabetic mice. The fact that oxidative stress performs a massive function in the development of diabetes and its complications has been widely recognized .…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates the growing social burden of diabetes. Diabetes mellitus can be associated with various complications, including retinopathy, neuropathy, renal failure, cardiovascular disease, and diabetic foot ulcers (DFUs) [ 3 ]. The incidence of DFUs is approximately 15–25% or even more [ 4 ].…”
Section: Introductionmentioning
confidence: 99%